Effects of adenosine triphosphate on vandetanib induced skin damage in rats. (1st October 2020) - Akagunduz, Baran; Ozcicek, Fatih; Kara, Ali Veysel; Guven, Deniz Can; Yazici, Gulce Naz; Çoban, Abdulkadir; Suleyman, Bahadır; Mammadov, Renad; Suleyman, Halis
Abstract: Purpose: Vandetanib is a wide spectrum tyrosine kinase inhibitor used for the treatment of metastatic medullary thyroid cancer (MTC) and various other cancer types. Although it is usually well-tolerated ıt has been linked to a variety of severe dermatologic reactions. Our study aimed was to investigate adenosine 5′-triphosphate (ATP) on vandetanib-induced skin damage. Materials and methods: A total number of 18 rats were divided into three equal groups as vandetanib group (VDB), vandetanib plus ATP group (VAT), and healthy group (HG); 25 mg/kg ATP was injected intraperitoneally (ip) to the VAT group. Normal saline was given to the HG and VDB groups as solvent via intraperitoneally. One hour later, 25 mg/kg vandetanib was applied orally via an orogastric catheter in the VAT and VDB groups. This procedure was repeated once daily for 4 weeks. After that period, all animals were sacrificed and their skin tissues removed. Malondialdehyde (MDA), total glutathione (tGSH), total oxidant status (TOS), total antioxidant status (TAS) levels in rats' skin tissues were evaluated with histopathological analyses. Results: MDA and TOS levels measured higher in the VDB group compared to the VAT and HG groups ( p < 0.001). tGSH and TAS levels of the VDB group measured lower than the VAT and HG groups ( p < 0.001). The structure and morphology of skin tissue were normal in the control group. In the VDB group, skin tissue damage with thinner epitelium, ruptured and degenerated hair follicles, abnormal accumulation of abnormal keratin on the epithelium and oedematous areas in the dermis was observed. In the VAT group, these findings were significantly improved. Conclusion: We demonstrated that adenosine triphosphate can prevent vandetanib-induced skin toxicity in rats for the first time. The promising results denote that further studies testing this agent in other animal models and in humans are warranted.